2020
DOI: 10.1155/2020/1362741
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Predictive Value of the Glasgow Coma Scale and the Kampala Trauma Score for Mortality and Length of Hospital Stay in Head Injury Patients at a Tertiary Hospital in Uganda: A Diagnostic Prospective Study

Abstract: Introduction. The prevalence rates of head injury have been shown to be as high as 25% among trauma patients with severe head injury contributing to about 31% of all trauma deaths. Triage utilizes numerical cutoff points along the scores continuum to predict the greatest number of people who would have a poor outcome, “severe” patients, when scoring below the threshold and a good outcome “non severe” patients, when scoring above the cutoff or numerical threshold. This study aimed to compare the predictive valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Other mechanisms such as assault (36.8%), fall (5.8%), and shooting (0.5%). 12 This was also found in several other studies where traffic accidents were still the main injury mechanism from 58% to 98.6%. 4,16,17 Faal for the cause of injury was mostly at the age of 0-17 years and age >55 years, 18 while in this study the average age of the patients was 36.41 years (SD±14.275).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Other mechanisms such as assault (36.8%), fall (5.8%), and shooting (0.5%). 12 This was also found in several other studies where traffic accidents were still the main injury mechanism from 58% to 98.6%. 4,16,17 Faal for the cause of injury was mostly at the age of 0-17 years and age >55 years, 18 while in this study the average age of the patients was 36.41 years (SD±14.275).…”
Section: Discussionsupporting
confidence: 72%
“…The median age was 30 years and the mean age was 32 years (SD ±11). 12 The mean of this study was also lower than a prospective multicenter study conducted in the Netherlands where the mean age was 47.3 ± 20.4 years with a mean severe brain injury of 46.1 ± 20.0 years. 16 In this study, the mean age of the subjects was lower due to differences in the inclusion criteria.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…9,10 Bununla birlikte GKS'nin, TBH sonrası mortalite ve hastanede kalış süresini tahmin etmede iyi performans gösterdiği, ancak uzun süreli sonuçları belirlemede yeterliliğinin yeniden gözden geçirilmesi gerektiği ve sonuca ilişkin prognostik değerinin hâlâ kanıtlardan yoksun olduğu rapor edilmiştir. 20,21 nuçlar arasında ilişkiyi değerlendiren bir çalışma, yaralanmadan 2 hafta sonra yapılan GKS'nin fonksiyonel sonuçlar ile ilişkili olduğunu not etmiştir. 22 Çalışmamızda, yaralanma üzerinden en az 6 ay geçen TBH'li hastalar, yaralanma sonrası ilk 24 saat içinde değerlendirilen GKS puanlarına göre orta ve ağır olarak gruplandırılmış, ağır TBH vakalarının orta düzey vakalarına göre günlük yaşam aktivitelerinde daha fazla fonksiyonel bağımlılık gösterdiği kaydedilmiştir.…”
Section: Discussionunclassified
“…The present study is the first to examine the difference between the four predictor variables in predicting mRS outcome at discharge in patients with TBI. Previous studies have compared GCS alone with GCS-P, Simplified Acute Physiology Score (SAPS) II, Acute Physiology and Chronic Health Evaluation (APACHE) II, Full Outline of UnResponsiveness (FOUR) score, and Kampala Trauma score in predicting the mortality among patients in neurocritical care or general critical care [30][31][32]. In a study by Brennan et al [17] that compared GCS alone with GCS-P in predicting mortality, it was found that GCS-P was significantly better than GCS in predicting mortality as increasing the GCS-P was associated with a decrease in mortality which is similar to the results of our study that also indicate that a 1 unit change in GCS-P is associated with a -0.17 units change in mortality.…”
Section: Discussionmentioning
confidence: 99%